2001
DOI: 10.1038/sj.ejcn.1601120
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary intakes and blood cholesterol concentrations at 31 months

Abstract: Objective: The initial stages of atherosclerosis have been shown to occur in children as young as 3. Elevated total and LDL cholesterol concentrations and low HDL concentrations are a well-established risk factor for atherosclerosis. The objective of this study was to investigate the dietary determinants of blood lipid concentrations at 31 months of age. Subjects: A randomly selected group of children (214 boys, 175 girls) in south-west England forming part of the Avon Longitudinal Study of Pregnancy and Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
(65 reference statements)
0
23
0
1
Order By: Relevance
“…Most studies included both boys and girls, except for one study in boys only ( 48 ) and one study in girls only ( 42 ) . Most studies were performed in Europe ( 20 23 , 29 , 36 , 38 , 40 , 42 , 49 , 50 , 52 , 53 , 57 , 59 , 61 , 64 , 65 , 75 ) , the USA or Canada ( 24 26 27 31 32 34 35 39 51 55 56 58 60 66 69 74 76 ) , and Australia or New Zealand ( 25 , 37 , 43 , 46 , 62 ) . Other studies were performed in populations in South or Central America ( 28 , 41 , 63 ) , South Africa ( 54 , 67 , 68 ) , Korea ( 44 ) , Russia ( 45 ) and Turkey ( 47 ) , and one study included subjects from the Philippines, Ghana and three European countries ( 48 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies included both boys and girls, except for one study in boys only ( 48 ) and one study in girls only ( 42 ) . Most studies were performed in Europe ( 20 23 , 29 , 36 , 38 , 40 , 42 , 49 , 50 , 52 , 53 , 57 , 59 , 61 , 64 , 65 , 75 ) , the USA or Canada ( 24 26 27 31 32 34 35 39 51 55 56 58 60 66 69 74 76 ) , and Australia or New Zealand ( 25 , 37 , 43 , 46 , 62 ) . Other studies were performed in populations in South or Central America ( 28 , 41 , 63 ) , South Africa ( 54 , 67 , 68 ) , Korea ( 44 ) , Russia ( 45 ) and Turkey ( 47 ) , and one study included subjects from the Philippines, Ghana and three European countries ( 48 ) .…”
Section: Resultsmentioning
confidence: 99%
“…We have also used this same methodology in the past and have shown significant relationships with biological outcomes. We have found associations between nutrient intakes at 18 and 31 months and haemoglobin, ferritin and blood lipid concentrations (Cowin et al. , 2001a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the understanding and control of determinants of plasma lipid levels in childhood is of utmost importance. With such aim in mind, several studies have identified significant associations between maternal anthropometric characteristics and lifestyle [6], and children’s characteristics such as gender [7][9], anthropometric characteristic [7], [9], early diet [8], [10], [11], and breastfeeding [12], with children’s plasma lipid levels. Genetic determinants appear to be relevant as well.…”
Section: Introductionmentioning
confidence: 99%